Analisis Yuridis Pertimbangan Hakim atas Gugurnya Perkara Cerai Talak dan Dampaknya terhadap Perlindungan Hukum Istri - Naufal Khuwaedi; Fitrohtul Khasanah; Imam Turmudi (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
In Religious Court proceedings, some divorce by talak cases lapse due to failure to pronounce talak as required by law, raising concerns over legal certainty and the rights of wives. This study examines the causes of lapsed Divorce of talak cases, analyses judicial reasoning in determining spousal maintenance obligations, and assesses the implications of such lapses for the legal protection of wives. The research employs a descriptive qualitative method with a normative legal approach. Primary data are derived from Case Number 1193/Pdt.G/2024/PA.Pwr, while secondary data consists of statutory regulations and relevant legal literature. The findings show that the lapse of the Divorce of talak case resulted from the petitioner’s failure to pronounce talak within the six months stipulated in Article 70, paragraph (6) of the Religious Courts Act. Judges based the determination of maintenance obligations on Article 80 paragraph (4) and Article 149 letters (a) and (b) of the Compilation of Islamic Law, supported by legal facts concerning neglect of maintenance and the parties’ economic conditions. The lapse of the case causes uncertainty regarding outstanding maintenance and marital status, resulting in psychological and social burdens for the wife. This study confirms that lapsed Divorce of talak cases have juridical implications for the legal protection of wives